Tracking Regulatory Mechanism of Trace Fe on Graphene Electromagnetic Wave Absorption - Zhang, Kaili; Liu, Yuhao; Liu, Yanan; Yan, Yuefeng; Ma, Guansheng; Zhong, Bo; Che, Renchao; Huang, Xiaoxiao (Nano-micro letters, 2024)
Highlights A carrier injection strategy is firstly proposed by designing Fe/reduced graphene oxide (RGO) heterogeneous interfacial material for giving full play to the dielectric dispersion properties of graphene. The electromagnetic wave absorption mechanisms mainly include enhanced conductance loss, dipole polarization and interfacial polarization. Outstanding reflection loss value (− 53.38 dB, 2.45 mm) and broadband wave absorption (7.52 GHz with only 2 wt% filling) of Fe/RGO composite were acquired, which is superior to single-component graphene. Polarization and conductance losses are the fundamental dielectric attenuation mechanisms for graphene-based absorbers, but it is not fully understood in revealing the loss mechanism of affect graphene itself. For the first time, the reduced graphene oxide (RGO) based absorbers are developed with regulatory absorption properties and the absorption mechanism of RGO is mainly originated from the carrier injection behavior of trace metal Fe nanosheets on graphene. Accordingly, the minimum reflection loss (RL min ) of Fe/RGO-2 composite reaches − 53.38 dB (2.45 mm), and the effective absorption bandwidth achieves 7.52 GHz (2.62 mm) with lower filling loading of 2 wt%. Using off-axis electron hologram testing combined with simulation calculation and carrier transport property experiments, we demonstrate here the carrier injection behavior from Fe to graphene at the interface and the induced charge accumulation and rearrangement, resulting in the increased interfacial and dipole polarization and the conductance loss. This work has confirmed that regulating the dielectric property of graphene itself by adding trace metals can not only ensure good impedance matching, but also fully exploit the dielectric loss ability of graphene at low filler content, which opens up an efficient way for designing lightweight absorbers and may be extended to other types materials.